Certain features of the examination of charred documents: international experience - Dikevych, Kristyna (Archives of Criminology and Forensic Sciences, 2025)
In modern forensic science, particular attention is given to the problem of recovering information from documents damaged by thermal exposure. The destruction of documents by burning is often used as a method of concealing criminal activity, which presents serious challenges for investigations. In this regard, the study of possibilities for restoring such documents acquires significant practical and theoretical importance. The aim of this article is to provide a comprehensive analysis of modern methods and approaches for examining burned documents within the framework of forensic technical expertise, taking into account the international experience of forensic experts in this field. The novelty of the study lies in the systematization and localization of methods from foreign scientific environments, which have not previously been presented in such a format. As a result, more than ten research methods were analyzed, which are effectively used by forensic experts in various countries for documents with different levels of damage. Recommendations are provided for choosing a specific method depending on the degree of charring of the document and the type of ink used. The conclusions emphasize the need for an interdisciplinary approach, the necessity of researching and combining various methods (physical, chemical, digital, etc.), as well as the need to improve methodological guidelines for experts in this field. The implementation of international experience in the Ukrainian practice of forensic technical examination of charred documents will contribute to increasing the effectiveness of information recovery and the quality of expert conclusions. Cooperation with international organizations and the adoption of advanced methodologies enhance the efficiency of examinations and ensure high-quality standards. The application of international practices in the study of charred documents can significantly improve the quality and effectiveness of forensic technical expertise in Ukraine. The use of modern methods and technologies, as well as international cooperation, are key factors for success in this area. The results of this research can be used to modernize the methodologies of forensic analysis of documents damaged by arson, taking into account contemporary scientific achievements and the needs of criminal justice. The proposed approaches will contribute to the unification of expert practice in Ukraine in accordance with international standards.